Peruntukan Lahan Kecamatan Temon Kabupaten Kulonprogo Pra dan Pasca Pembangunan Bandara Internasional Yogyakarta - Nurkukuh, Dwi Kunto; Candra Ragil (ReTII, 2022)
Development is one of the ways the government does to improve people’s welfare. However, development can have both positive and negative impacts. One of the impacts is the change of land use. In 2017, the Yogyakarta International Airport (YIA) was built in Temon District, Kulonprogo Regency. There are still many agendas for developing airport land and around the airport in the years to come, so it is necessary to study how the land use changes before and after the airport construction in Temon District. This research belongs to the type of qualitative descriptive research. The phenomenon studied is the change in land use in Temon District, Kulonprogo Regency before and after the construction of Yogyakarta International Airport. This study uses data collection techniques in the form of examination of documentation and observation techniques. Documentation checks are carried out by collecting satellite images of Temon District and document data related to the land use of Temon District. The observation technique was carried out by observing directly the land use in Temon District. From the analysis of the maximum likelihood classification, it shows that in 2022 there will be a change in land use, namely the addition of an airport, which was previously rice fields, ponds and settlements. This transition to an airport causes the area of â€‹â€‹rice fields, ponds and settlements to decrease in 2022 when compared to 2017. Mixed gardens have decreased from 2012-2022. Settlements had increased from 2012-2017, but decreased in 2017-2022. Agriculture Dry land and rice fields is decreasing from 2012-2022. Ponds had increased from 2012-2017, but decreased in 2017-2022. Open land had decreased from 2012-2017, but increased in 2017-2022.